1938
DOI: 10.1113/expphysiol.1938.sp000765
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Modification of the Accessory Sexual Apparatus in the Hen

Abstract: 1. Peculiarities of form and function in the accessory sexual apparatus of a number of experimental pullets, derived from eggs injected with œstrone at an early stage of incubation, are described and discussed. 2. Only one of a group of 6 females laid normal eggs when sexually mature, the remainder producing eggs devoid of shell or lacking both shell and egg membranes. This phenomenon is ascribed to an abnormality of the oviduct. 3. All the experimental birds autopsied possessed two oviducts which showed incom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0
1

Year Published

1947
1947
2003
2003

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 3 publications
2
12
0
1
Order By: Relevance
“…Sterility was more prevalent among those female quail receiving the highest levels of mestranol (Table 1) suggesting that the response is dose dependent. As noted by other investigators (Greenwood and Blyth, 1938;, steroid sterilized birds frequently laid soft-shelled eggs ( Table 1).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Sterility was more prevalent among those female quail receiving the highest levels of mestranol (Table 1) suggesting that the response is dose dependent. As noted by other investigators (Greenwood and Blyth, 1938;, steroid sterilized birds frequently laid soft-shelled eggs ( Table 1).…”
Section: Discussionsupporting
confidence: 77%
“…Feeding quail early in life with mestranol causes a change in reproductive function similar to that observed after treatment of birds eggs with steroids (Greenwood and Blyth, 1938;Snedecor, 1949, van Tienhoven, 1957. Wentworth (1968) has reported a similar sterilizing action after young quail consume synthetic grit containing mestranol.…”
Section: Discussionsupporting
confidence: 54%
“…Earlier studies have also shown that embryonic exposure to oestrogen (Greenwood and Blyth 1938;Rissman et al 1984) or o, p'-DDT (Bryan et al 1989) results in the production of soft-shelled or shell-less eggs. CA appears to play a crucial role in eggshell formation since inhibition of this enzyme decreases shell quality (Gutowska and Mitchell 1945;Mueller 1962;Bernstein et al 1968;Lundholm 1990).…”
Section: Discussionmentioning
confidence: 94%
“…In females, the left oviduct is not grossly altered, but an abnormally large right oviduct may be retained. Functional changes in the left oviduct and shell gland may occur when female chicks reach adulthood, as exposed birds lay eggs with defective, thin, or soft shells (42).…”
Section: Sexual Differentiation Of Birds and Mammalsmentioning
confidence: 99%